Factor XI and Protection of the Fibrin Clot against Lysis – a Role for the Intrinsic Pathway of Coagulation in Fibrinolysis - Bouma, Bonno N.; von dem Borne, Peter A. Kr.; Meijers, Joost C. M. (Thrombosis and Haemostasis, 1998)
Blood coagulation is an important mechanism that maintains the integrity of the vascular system to prevent blood loss after injury. The conceptions on the working mechanism of coagulation are based on the waterfall or cascade model, which was already proposed more than 30 years ago, independently by Davie and Ratnoff (1) and MacFarlane (2). Blood coagulation was viewed as a series of linked proteolytic reactions in which zymogens are converted into serine proteases, ultimately leading to the formation of thrombin, which converts soluble fibrinogen into insoluble fibrin. Coagulation was thought to proceed via two pathways, an extrinsic and an intrinsic pathway. Activation of the extrinsic pathway of coagulation occurs by the exposition of tissue factor at the site of injury (3) whereas the intrinsic system is activated after exposure of plasma to an activating surface. Although the in vivo activating surface is unknown, the contact system was believed to play a role in the initiation of the intrinsic pathway. This system consists of factor XII, prekallikrein, high molecular weight kininogen and factor XI. The physiological relevance of the contact system is unclear, since a deficiency of factor XII, prekallikrein or high molecular weight kininogen does not result in a bleeding disorder. In contrast, patients deficient in factor XI, most common among Ashkenazi Jews, do suffer from variable bleeding abnormalities especially from tissues with high local fibrinolytic activity (urinary tract, nose, oral cavity, tonsils) (4, 5). This suggested there was an alternative route for the activation of factor XI, and recently such a route was described (6, 7). Thrombin was found to activate factor XI, even in the absence of a negatively charged surface (6-11), and factor XI was shown to play a role in the protection of the fibrin clot against lysis (9). In plasma the possibility cannot be excluded that the activation of factor XI by thrombin takes place via an intermediary component. Recently, it was shown that meizothrombin was capable of activating factor XI (12).